2019
DOI: 10.1186/s40425-019-0767-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signatures for quick diagnosis of life-threatening infection during the CAR T-cell therapy

Abstract: BackgroundChimeric antigen receptor-modified (CAR) T-cell immunotherapy is a novel promising therapy for treatment of B-cell malignancy. Cytokine release syndrome (CRS) and infection are the most common adverse events during CAR T-cell therapy. Similar clinical presentation of concurrent CRS and infection makes it difficult to differentially diagnose and timely treat the condition.MethodsWe analyzed the features of infection events during the first 30 days after CAR T-cell infusion (CTI) in 109 patients from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 28 publications
4
75
0
1
Order By: Relevance
“…Other risk factors for infection after CAR T cell therapy shown by previous studies included higher number of prior treatments, higher doses of CAR T cells, older age, previous history of infection, and CD22-specific CAR T cells 5 , 8 . Finally, a recent study described the association between double peak IL-6 pattern (second surge of serum IL-6 after initial normalization) and life-threatening infection 26 . Along with the current interest of anti-IL6 therapy in severe acute respiratory syndrome coronavirus 2 patients with respiratory failure 27 – 34 , it is at least worth noting that we did not observe an association between the use of tocilizumab and infections in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for infection after CAR T cell therapy shown by previous studies included higher number of prior treatments, higher doses of CAR T cells, older age, previous history of infection, and CD22-specific CAR T cells 5 , 8 . Finally, a recent study described the association between double peak IL-6 pattern (second surge of serum IL-6 after initial normalization) and life-threatening infection 26 . Along with the current interest of anti-IL6 therapy in severe acute respiratory syndrome coronavirus 2 patients with respiratory failure 27 – 34 , it is at least worth noting that we did not observe an association between the use of tocilizumab and infections in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analyses, the use of systemic corticosteroids for the management of CRS or ICANS has emerged as a major risk factor of infection [ 18 ]. Certain inflammatory signatures – such as the “double peaks of IL-6” pattern observed in our patient – have been shown to confer an especially high risk of life-threatening infection [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although there are drugs that can control CRS, complications remain a barrier to standard treatment. It has been demonstrated that the degree of CRS severity is associated with disease burden at the time of infusion, as a higher tumor burden results in more serious CRS (45), suggesting that in the case of low tumor burden, such as early disease, the risk and severity of CRS in patients undergoing CAR T-cell therapy may be markedly reduced. Therefore, in the present study, radiotherapy was used prior to CAR T-cell therapy, successfully decreasing the tumor burden of the patient.…”
Section: Discussionmentioning
confidence: 99%